2023
DOI: 10.1136/bmjopen-2022-067126
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the effectiveness of interventions to reduce mental health related stigma in the workplace: a systematic review

Abstract: ObjectivesIncreasing access to mental health support is a key factor for treating mental disorders, however, important barriers complicate help-seeking, among them, mental health related stigma being most prominent. We aimed to systematically review the current evidence for interventions focusing on reducing stigma related to mental health problems in small and medium enterprises (SMEs).DesignSystematic review with a focus on interventions targeting mental health related stigma in the workplace in accordance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…We obtained and invested even more on the anti-stigma materials which include multiple intervention techniques such as psychoeducation, interactive skills training exercises, and peer support activities. These materials are able to contribute to structural changes in the SMEs such as the promotion of communication strategies for supporting employees, the creation of a more inclusive working environment leading to lower levels of personal (self-stigma) and perceived (social) stigma and, respectively, to more positive mental health outcomes (Tóth et al 2023 ). Importantly, our intervention which was delivered totally online shows the ability to achieve mental health outcomes in the working sectors of SMEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We obtained and invested even more on the anti-stigma materials which include multiple intervention techniques such as psychoeducation, interactive skills training exercises, and peer support activities. These materials are able to contribute to structural changes in the SMEs such as the promotion of communication strategies for supporting employees, the creation of a more inclusive working environment leading to lower levels of personal (self-stigma) and perceived (social) stigma and, respectively, to more positive mental health outcomes (Tóth et al 2023 ). Importantly, our intervention which was delivered totally online shows the ability to achieve mental health outcomes in the working sectors of SMEs.…”
Section: Discussionmentioning
confidence: 99%
“…SMEs are particularly vulnerable because they are often limited in their capacity to initiate mental health interventions due to lack of resources, time, knowledge and personnel (De Angelis et al 2020 ; Beck and Lenhardt 2019 ), but there is also evidence showing that the lack of complex bureaucratic processes, the feeling of personal accountability, and the potential of teamwork development are elements that can be found in SMEs and are able to facilitate the implementation and efficacy of mental health interventions (McCoy et al 2014 ). Despite the interesting contextual characteristics of the SMEs and the fact that they are the backbone of Europe’s economy (Wymenga et al 2011 ), the literature on mental health interventions implemented in smaller occupational settings is scarce especially for sectors such as Healthcare that usually consist of larger workforces (Tóth et al 2023 ; Greiner et al 2022 ; B. Hogg et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are many current universal workplace interventions targeted at addressing workplace stigma to help meet the needs of workers living with suicidal thoughts and behaviours or mental health problems. For example, a recent review found that anti-stigma programs designed to suit various workplace contexts resulted in positive outcomes [ 58 ]. In Australia, programs such as Mental Health First Aid, Mates in Construction and Living Works Australia all offer various interventions, including gate-keeper programs, tailored to workplaces.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings show that concerns about experiencing discrimination and other negative repercussions related to being open about or seeking support for mental health at work suggests the potential value of targeted anti-stigma campaigns and interventions to promote a culture of openness and promote help-seeking at work. Evidence suggests that anti-stigma campaigns can improve comfort with disclosing mental health issues, including with employers [ 31 ] and can improve supportive behaviour among workers [ 32 , 33 ]. Interventions based on social contact among people without and with lived experience of mental health condition are identified as highly effective in reducing mental health stigma [ 34 ].…”
Section: Discussionmentioning
confidence: 99%